Instrumental tactile diagnostics in robot-assisted surgery - Solodova RF (Dove Medical Press, 2016)
Rozalia F Solodova,1,2 Vladimir V Galatenko,1,2 Eldar R Nakashidze,3 Igor L Andreytsev,3 Alexey V Galatenko,1 Dmitriy K Senchik,2 Vladimir M Staroverov,1 Vladimir E Podolskii,1,2 Mikhail E Sokolov,1,2 Victor A Sadovnichy1,2 1Faculty of Mechanics and Mathematics, 2Institute of Mathematical Studies of Complex Systems, Lomonosov Moscow State University, 31st Surgery Department, Clinical Hospital 31, Moscow, Russia Background: Robotic surgery has gained wide acceptance due to minimizing trauma in patients. However, the lack of tactile feedback is an essential limiting factor for the further expansion. In robotic surgery, feedback related to touch is currently kinesthetic, and it is mainly aimed at the minimization of force applied to tissues and organs. Design and implementation of diagnostic tactile feedback is still an open problem. We hypothesized that a sufficient tactile feedback in robot-assisted surgery can be provided by utilization of Medical Tactile Endosurgical Complex (MTEC), which is a novel specialized tool that is already commercially available in the Russian Federation. MTEC allows registration of tactile images by a mechanoreceptor, real-time visualization of these images, and reproduction of images via a tactile display. Materials and methods: Nine elective surgeries were performed with da Vinci™ robotic system. An assistant performed tactile examination through an additional port under the guidance of a surgeon during revision of tissues. The operating surgeon sensed registered tactile data using a tactile display, and the assistant inspected the visualization of tactile data. First, surgeries where lesion boundaries were visually detectable were performed. The goal was to promote cooperation between the surgeon and the assistant and to train them in perception of the tactile feedback. Then, instrumental tactile diagnostics was utilized in case of visually undetectable boundaries. Results: In robot-assisted surgeries where lesion boundaries were not visually detectable, instrumental tactile diagnostics performed using MTEC provided valid identification and localization of lesions. The results of instrumental tactile diagnostics were concordant with the results of intraoperative ultrasound examination. However, in certain cases, for example, thoracoscopy, ultrasound examination is inapplicable, while MTEC-based tactile diagnostics can be efficiently utilized. Conclusion: The study proved that MTEC can be efficiently used in robot-assisted surgery allowing correct localization of visually undetectable lesions and visually undetectable boundaries of pathological changes of tissues. Keywords: tactile feedback, instrumental palpation, Medical Tactile Endosurgical Complex, tactile lesion localization